The organizational production of earnings inequalities, Germany 1995–2010 - Donald Tomaskovic-Devey; Silvia Maja Melzer; Semih Tumen (PLoS ONE, 2020)
Germany has experienced sharply rising earnings inequalities, both between and within workplaces. Working from prior literature on rising employment dualization and the fissuring of workplaces into high and low wage employers, we explore a set of organizational explanations for rising between and within workplace inequality focusing on the role of employment dualization, skill segregation/complexity, and firm fissuring. We describe and model these hypothesized processes with administrative data on a large random sample panel of German workplaces. We find that rising inequalities are associated with polarization in industrial wage rates and the birth of new low wage workplaces, as well as increased establishment skill specialization and the growth of part-time jobs in workplace divisions of labor. We conclude with recommendations for future research that directly examines more proximate mechanisms and their relative importance in different institutional contexts.